Non-disruptive Data Mitigation through Storage Virtualization - Manchanda, Pankaj; Jain, Rachna (International Journal of Computer Sciences and Engineering, 2014)
Storage Area Network provides (SAN) matures larger and wide complexity to implement secure and robust communication between host and storage device in storage infrastructure to consolidate data and utilizing storage resources effectively. To adapt this virtualization in storage makes SAN to enhanced productivity, assets utilization and better management of storage infrastructure. Storage virtualization simplifies resource management by pooling and sharing resources for physical infrastructure to logical-view infrastructure by storage utilization and modifying storage without affecting an applicationï¿½s availability and non-disruptive Data mitigation to access and storage while migration of data-exchange in progress.